Using remainder value theorem, the value of f(3) is 3
Solution:
Given, function is
![f(x)=-x^(3)+4 x^(2)-2 x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/j8b9afmrubq4ptniw122po8z6ajaeo9v80.png)
We have to find the value of f(3) by using remainder theorem.
Now, we have to divide f(x) with x – 3, because we want value of f(3)
If we want f(a), then we have to divide with x – a.
Now, first let us factorize the f(x)
![\begin{array}{l}{\text { Then, } f(x)=-x^(3)+4 x^(2)-2 x} \\\\ {=-x\left(x^(2)-4 x+2\right)} \\\\ {=-x\left(x^(2)-4 x+3-1\right)} \\\\ {=-x\left(x^(2)-3 x-x+3-1\right)} \\\\ {=-x(x(x-3)-1(x-3)-1)} \\\\ {=-x((x-3)(x-1)-1)} \\\\ {=-x(x-3)(x-1)+x}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rtit7632gnwpkmerp123q2m106jen9ijt6.png)
Now, let us divide the f(x) with x – 3
![\begin{array}{l}{\rightarrow \frac{-\mathrm{x}(\mathrm{x}-3)(\mathrm{x}-1)+\mathrm{x}}{x-3}=(-x(x-3)(x-1))/(x-3)+(x)/(x-3)} \\\\ {=-\mathrm{x}(\mathrm{x}-1)+(x-3+3)/(x-3)} \\\\ {=-\mathrm{x}(\mathrm{x}-1)+1+(3)/(x-3)}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tal2b80dsq0xigawjugi3spn7zcwaw3er4.png)
Now, multiply f(x) with (x -3) ⇒ (-x(x -1) + 1)(x -3) + 3
This is in the form of:
![\text {quotient } * \text { divisor }+\text { remainder.}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/eu8t9g7ckkki6d47epcvdb7ljout5a1rq8.png)
Hence, the remainder is 3.
Therefore the value of f(3) is 3